Oryzalin but not Itraconazole disrupts CTP synthase localization in some Toxoplasma gondii tachyzoites (2017)
Toxoplasmosis is a worldwide prevalent infection caused by the Toxoplasma gondii parasite, that could lead to several diseases especially in new-borns and immunocompromised patients, therefore, discovery of novel drug targets has become a major concern. The pyrimidine pathway has been proposed as a possible drug target, since apicomplexan enzymes vary from those of humans. Previous studies have shown that inhibition of CTP synthase with the glutamine antagonist 6-diazo-5-oxo-L-norleucine (DON), disrupts tachyzoites' morphology and reduces significantly the infection progression. A similar phenomenon has been described with inhibitors such as oryzalin and itraconazole but the exact mechanism has not been clearly elucidated yet. Consequently, the aim of this study was to determine if CTP synthase is affected by the inhibition effect during treatment with oryzalin and itraconazole. T. gondii tachyzoites were cultured in HFF cells and treated with 2 uM Itraconazole, 0.5 and 2.5 uM oryzalin, or 30 uM DON, or with combinations of inhibitors. Infected host cells were fixed 28 hours post infection and CTP synthase localization was assessed using immunofluorescence. Parasites treated with itraconazole alone or in combination with DON did not display any significant differences in enzyme localization compared to those observed in control treatments. However, incubation with oryzalin appeared to affect CTP synthase distribution since protein aggregates tended to localize towards the sides of some of the tachyzoites. These results suggest that CTP synthase might be involved in parasite morphology but stronger evidence is needed.